Advancements in polymeric biomaterials for In vitro expansion of hematopoietic stem cells: a scoping review - Rahmat Sam, Mohd Fuad; Ismail, Muhammad Azamuddin (IIUM Press, 2026)
Background: A thorough source of HSPCs with a reduced risk of graft host disease (GVHD) is umbilical cord blood (UCB). Nevertheless, compared to peripheral blood or bone marrow stem cells, hematopoietic stem cells (HSCs) isolated from single cord blood are less common and require longer to settle in the bone marrow before they may begin generating blood cells. Earlier clinical trials were conducted to ensure bone marrow (BM) sustainability through the application of various natural and synthetic polymeric techniques. Usage of polymeric biomaterials can be seen as alternative to stabilise stem cell-based therapies currently. Therefore, this article aims to evaluate the data progress and compile the evidence of current advances of polymeric biomaterial for in vitro expansion of HSCs. Methods: Articles were found through four electronic search engines using five keywords. The article selection followed Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines. Articles were included if they met the following criteria: (1) full text articles between 2019 until 2023; (2) specific keywords must have in the research articles; (3) published in English; (4) qualitative or quantitative study. Studies were excluded if they were review articles, chapter books, systematic review, discussion papers and did not match with study objectives. Results: A total of 5194 articles were screened, and 52 full-text articles were evaluated. There were 37 articles that did not match with the inclusion and exclusion criteria and had been excluded because the paper involved review paper and did not discuss the usage of biomaterials for expansion of HSCs. Lastly, only 15 articles were selected for scoping review analysis. Conclusion: The findings reveal that cultured polymeric biomaterials have had a significant impact on the stability and integrity of HSCs. Besides, the selected polymeric biomaterials can improve crosstalk or cell-cell interaction through laboratory settings. From this review, it can be concluded that the approach used by researchers truly aids the clinical institution to overcome the deficiency in stem cell therapies.